Dark Reflections: Fantasy and Duality in the Work of David Lynch - Boyd, Nolan Heyward (Wake Forest University, 2014)
This thesis investigates the sexual construction of Lacanian fantasy in the work of David Lynch. Primary texts include Lynch's films Blue Velvet (1986), Twin Peaks: Fire Walk with Me (1992), Lost Highway (1997), and Mulholland Drive (2001), along with David Lynch and Mark Frost's TV show Twin Peaks (1990-1991). The thesis builds upon the Lacanian scholarship of Lynch scholar Todd McGowan, examining how fantasy operates and structures the worlds of Lynch's films; the thesis expands upon McGowan's work from a feminist perspective, considering how concerns of gender and sexuality inform the construction of fantasy in Lynch's work. In Blue Velvet and Twin Peaks, fantasy operates as a necessary element of social structure; the social experience of reality is informed by the existence of fantasy in these texts. Lost Highway and Mulholland Drive turn from the social to the personal, examining how desperate individuals seek escape from their unbearable realities through an escape into fantasy. As this thesis will investigate, although fantasy is a necessary component of the social order, it is inadequate as a means of escape from the troubles of life.
Keywords: David Lynch; Duality; Fantasy; Gender; Lacan; Psychoanalysis